Relationship between individuals’ levels of pain, physical activity and problematic internet use in the covid-19 pandemic - Özüdoğru, Anıl; Baltacı, Önder; Dalakçı, Muhammed Samed; Akbulut, Ömer Faruk (Journal of Dependence, 2021)
Objective: The aim of this research is to examine the role of sex with physical activity and problematic internet use as predictors of pain levels caused by individuals ’ use of technology during the covid-19 pandemic. Method: The research was carried out by relational screening method. The participants of the study are 296 adult individuals over the age of 18 living in Turkey, 198 of whom are female (66.9%) and 98 of whom are male (33.1%), who use the internet actively. In the study, "Problematic Internet Use Scale-Short Form-6", "International Physical Activity Questionnaire - Short Form" and "Personal Information Form" were used. Results: A negatively significant association was found between pain levels and physical activity levels caused by individuals ’ use of technology during the COVID-19 pandemic, while a positively significant association was found between problematic internet usage levels. In addition, gender, physical activity, and problematic internet use variables were found to together explain 18.3% of the total variance in pain caused by technology use. Conclusion: During the pandemic period, physical activity, problematic internet use and gender factors were found to have an important place in the level of pain caused by individuals ’ use of technology.